Investigating printability of hydrogel and hydrogel nano composite for bioelectronics - Muhammad Izz Khan Bin Ayub Khan (Nanyang Technological University, 2023)
The significance of bioelectronics research lies in its potential to revolutionize the way we diagnose and treat diseases, monitor our health, and interact with the environment. Despite the promising potential of bioelectronics, there are still several research gaps that need to be addressed. One of the main challenges is the development of biocompatible and stable materials that can be integrated with biological systems without causing adverse effects. Another challenge is the need for a better understanding of the complex interactions between electronic devices and biological systems, and how they can be optimized to achieve the desired outcomes. Moreover, there is a need for more interdisciplinary research that bridges the gap between engineering and biology, and the development of more advanced manufacturing techniques for bioelectronics devices. The research gaps in bioelectronics present opportunities for scientists and engineers to develop innovative solutions that could have a profound impact on human health and the environment. Investigating the Printability of Hydrogel and Hydrogel Nano Composite for Bioelectronics is a research study that aims to optimize the printing process of hydrogel and hydrogel nanocomposites using the aerosol jet printing method. The study focuses on investigating the printability of these materials by analysing and characterizing their structural, mechanical properties biocompatible properties, and optimizing the printing parameters to achieve high-resolution and accurate printed structures for bioelectronics applications. Specifically, alginate hydrogels, as they are a promising material for bioelectronics due to their biocompatibility and ability to retain moisture. However, their printability using aerosol jet printing has not been extensively studied. Alginate hydrogels with graphite have also gained interest due to their potential for enhanced electrical conductivity. The results showed that lower sheath and ink flow rates resulted in smaller and more consistent droplets, depending on the initial ink flow rate, leading to higher resolution prints with rough surface area and graphite particles. The addition of graphite to the hydrogel improved the electrical conductivity of the printed structures. This study can help in the development of flexible, biocompatible, and electronically active devices for use in various biomedical applications, such as biosensors, implantable medical devices, and tissue engineering. The study can provide valuable insights into the printing parameters, materials, and fabrication techniques needed to create precise and reliable structures for these applications.